Vegetative Growth Response of Soybean (Glycine max L. Merril) After Applicated Several Plant Growth Regulators (PGRs) - Mangais, Rowland; Rampe, Henny L.; Siahaan, Parluhutan (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2022)
Vegetative growth of plants can be influenced by internal factors including hormones (Plant Growth Regulators). The purpose of the study is to determine the growth response of soybean ( Glycine max L.Merril) after application of some plant growth regulators (PGRs). The research method used was Completely Randomized Design (CRD). There were four levels of extract concentration that were applied namely P0: Control, P1: onion extract, P2 bamboo shoot extract, and P3: banana weevil extract. Data of the growt parameters were analyzed with ANOVA (Analysis of Variance) and continued with LSD 0.05 test. Results of the study showed that the application of PGRs from extracts of onion , bamboo shoots and banana weevil give the increase of growth in height of plants in 15 days after planting, fresh weight, dry wight and root volume of soybean (G. max). Application of PGRs couldn’t give any effect in high, number of leaves and ratio of canopy roots 27 days after planting.Keywords : Glycine max L. Merril , Vegetative growth, and Plant Growth Regulators (PGRs